Diabetes and cardiovascular disease : evaluation, prevention, and management - Wong, Nathan D.; Malik, Shaista (Jaypee Brothers Medical Publishers (P) Ltd., 2015)
Diabetes and Cardiovascular Disease: Evaluation, Prevention & Management presents the epidemiologic relation of diabetes and associated risk factors with cardiovascular disease. This concise guide demonstrates the role of non-invasive imaging strategies for evaluation of cardiovascular disease risk in diabetes, and the role of nutrition and physical activity in preventing diabetes and its cardiovascular complications.